Unveiling the Influence of the Curve of Spee on Bite Force and Chewing Ability: A Comparative Study - Zainab Ali Alkhalaf; Mohammed Ghazi Sghaireen; Kiran Kumar Ganji; Mohammad Khursheed Alam; Rakhi Issrani; Raghad Mohammed Alsaleh; Sultana Zamil Almegren; Mahmoud Gamal Salloum (International Journal of Clinical Practice)
Aim. To investigate the impact of the curve of Spee (CS) accentuation on bite force, chewing ability, and additionally, other factors that influence chewing ability and bite force such as restorations, caries, gender, habits, and TMJ problems. Materials and Methods. 231 participants (118 male and 113 female, mean age = ±27.96 years) were recruited for this cross-section study. Participants completed a data collection sheet in which age, gender, Angle’s classification of malocclusion, overjet, overbite, TMJ problems, habits, restorations, and caries experience were recorded. Two examiners made a lower impression, chewing ability test and measured the bite force for each participant. Measurement of the CS was obtained digitally from the poured dental cast, and the categorization was as follows: flat (<1 mm), normal (1-2 mm), or deep (>2 mm). Results. The mean maximum bite force (MBF) was 468.722 N for participants with flat CS, 389.822 N for normal CS, 647.08 N for deep CS, and 384.667 N for reverse CS. The average MBF was higher for participants with deep CS (p<0.05). MBF force was higher in males. However, BMI was not significantly related to MBF values. Participants with normal and flat CS have comparable chewing capacity (p>0.05). Also, a significant difference in bite force and chewing ability was found between the three categories of CS (p<0.05). Conclusion. Bite force variations across various CS types were linked to gender and habits. Chewing ability showed no differences concerning gender, habits, TMJ problems, caries, or restorations, emphasizing CS’s significant impact on bite force while showcasing the unchanged nature of chewing ability amidst diverse factors.